Complication rates following all-epiphyseal ACL reconstructions in skeletally immature patients: A retrospective case series study. Issue 47 (24th November 2021) - Saad, Lydia; Grimard, Guy; Nault, Marie-Lyne
Abstract : Abstract: The aim was to evaluate the safety of a physeal-sparing anterior cruciate ligament reconstruction technique (ACLR), performed with Orthopediatrics (Warsaw, IN) equipment, by assessing complications. Skeletally immature patients who underwent all-epiphyseal ACLR between 2015 and 2017 with postoperative follow-up were included in this retrospective study. Complications, demographic, clinical, surgical, and imaging data was retrieved from an urban tertiary pediatric hospital database. Physeal status, limb-length discrepancies (LLD), and angular deformities were assessed on preoperative and postoperative radiographs, growth disturbances were reported, and initial and follow-up diameters of tunnels were compared. Nineteen ACLRs were included from 18 patients, 4 females and 14 males, with bone age at surgery of 13.3 ± 1.0 years. At a mean follow-up of 19.2 ± 10.1 months, there were no symptomatic growth disorders requiring intervention. There were: 2 (11.1%) unilateral early physeal closures, 2 (10.5%) new angular deformities (5°–10°), 4 (22.2%) LLD (1–2 cm), 1 (5.6%) contralateral ACLR, 1 (5.6%) femoral screw removal, 2 (10.5%) graft ruptures, and 1 meniscal tear (5.3%). Mean tunnel widening was 1.7 mm and 1.5 mm on the femoral and tibial side, respectively, and no massive osteolysis was recorded at the polyetheretherketone implant site. The complication rates were comparable to those in similar studies, with no growth-related complications at 19.2 months.